Intestinal constipation in the elderly and associated factors – SABE Study - Gomes,Sâmia (2019)
ABSTRACT Introduction: Constipation is understood to be a chronic problem related to a multi-functional disorder that affects approximately 20% of the world population, and it is more prevalent in women and in the elderly. Objective: To measure the prevalence of intestinal constipation in elderly people living in São Paulo, as well as the factors associated with this condition. Methods: This was a cross-sectional study using the SABE study database (Health, Well-being and Ageing) from 2010 with a probabilistic sample of 1345 elderly people (≥ 60 years) living in São Paulo city, both male and female. Logistic regression was used to identify factors associated with intestinal constipation. Results and conclusion: The prevalence of intestinal constipation in older people is 14.23%. The associated factors were joint pain, osteoporosis, and use of laxatives; in women, associated factors were antidepressants and diuretics.